(untitled) (Swiss Medical Weekly, 2010)
QUESTIONS UNDER STUDY / PRINCIPLES: The value of postoperative pro-calcitonin (PCT) in the follow-up of patients with localised infections in the orthopaedic domain is unknown. METHODS: We conducted a retrospective study comparing postoperative ultra-sensitive serum PCT (upper normal level 0.25 µg/l) and C-reactive protein (CRP; upper normal level 10 mg/l) levels in adult patients with localised non-bacteremic orthopaedic infections. RESULTS: A total of 165 paired PCT and CRP samples were retrieved from 60 infected patients. PCT levels exceeded normal in only half of the patients and practically only on the first postoperative day, despite a clinically active infection in all cases. PCT values did not differ between patients with or without surgical re-interventions (36 patients; median 0.09 mg/l vs. 24 patients; median 0.08 µg/l; Wilcoxon-rank sum-test, p= 0.34). CRP was elevated in 54 patients (90%) with a maximum at day 2, and normalised by the tenth day. Both markers correlated poorly with each other (Kendall-tau-test 0.47). The cost for one analysis (phlebotomy by nurses, transport and laboratory) was US70 for PCT and 20 for CRP. CONCLUSIONS: Postoperative serum PCT levels in orthopaedic infections were rarely elevated, even if patients continued to be infected. They quickly fell to within a normal range at day 2. PCT does not seem to be better than the less expensive CRP in the follow-up of these patients.